If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3w + -1(7w + 12) = 2(w + 3) Reorder the terms: 3w + -1(12 + 7w) = 2(w + 3) 3w + (12 * -1 + 7w * -1) = 2(w + 3) 3w + (-12 + -7w) = 2(w + 3) Reorder the terms: -12 + 3w + -7w = 2(w + 3) Combine like terms: 3w + -7w = -4w -12 + -4w = 2(w + 3) Reorder the terms: -12 + -4w = 2(3 + w) -12 + -4w = (3 * 2 + w * 2) -12 + -4w = (6 + 2w) Solving -12 + -4w = 6 + 2w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-2w' to each side of the equation. -12 + -4w + -2w = 6 + 2w + -2w Combine like terms: -4w + -2w = -6w -12 + -6w = 6 + 2w + -2w Combine like terms: 2w + -2w = 0 -12 + -6w = 6 + 0 -12 + -6w = 6 Add '12' to each side of the equation. -12 + 12 + -6w = 6 + 12 Combine like terms: -12 + 12 = 0 0 + -6w = 6 + 12 -6w = 6 + 12 Combine like terms: 6 + 12 = 18 -6w = 18 Divide each side by '-6'. w = -3 Simplifying w = -3
| 125+18=200+12 | | 39+9x=-15 | | 9x+19=3x+17 | | (-44)+(-32)= | | w-18=-17 | | 8(w+9)-(-2w-3)=9w | | T+2(t-4)=5(1-2t) | | 10x+72=9x+80 | | (7x+6)(8x^2+5x+3)= | | 1=g+3 | | 48x-13-24=131 | | r+15=-34 | | 48-13-24=131 | | -(4x-14)+3(3x+4)= | | 3x-54=2x-9 | | r+15=-41 | | 48-12-24=131 | | w+(-12)=-41 | | .05x+x=32.14 | | -43+6x=-103 | | -3(2x-y)=-3(-1) | | 60+8f=-180 | | 5+(-8)-2= | | nn=81 | | 36p=36 | | x/2-9=-23 | | 8n+3-4n-n+11=14 | | 2x+34x=-60 | | 2(3x+y)=2(-9) | | -5b-7=38 | | -4a-2a+5+-9=44 | | 3(2x+3)=48 |